2016
DOI: 10.1017/s1355617716001004
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences in Emotion Recognition in Multi-concussed Athletes

Abstract: Male concussed athletes were significantly impaired in recognizing negative emotions and needed more emotional intensity to correctly identify these emotions, compared to same-sex controls. In contrast, female concussed athletes performed similarly to same-sex controls. These findings suggest that sex significantly modulates concussion effects on emotional facial expression recognition. (JINS, 2017, 23, 65-77).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 125 publications
1
11
0
Order By: Relevance
“…These findings suggest that multiple concussions alter the dominant right-hemisphere response to early EFE processing (Batty & Taylor, 2003; Eimer & Holmes, 2007; Halit et al, 2000; Itier & Taylor, 2002). This right-hemisphere dominance suppression in early stages of EFE processing found in multi-concussed athletes could contribute to the known persistent alterations of the ability to identify and discriminate emotions in multi-concussion athletes (Léveillé et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These findings suggest that multiple concussions alter the dominant right-hemisphere response to early EFE processing (Batty & Taylor, 2003; Eimer & Holmes, 2007; Halit et al, 2000; Itier & Taylor, 2002). This right-hemisphere dominance suppression in early stages of EFE processing found in multi-concussed athletes could contribute to the known persistent alterations of the ability to identify and discriminate emotions in multi-concussion athletes (Léveillé et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…A recent study demonstrated significant sex-related differences on the processing of emotional stimuli after concussion (Léveillé et al, 2016). Whereas emotion recognition ability was equivalent in female athletes regardless of concussion history, male concussed athletes showed emotion recognition alterations and needed significantly more emotional intensity than unconcussed male counterparts to identify these emotions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Léveillé et al (52) reported emotion recognition scores for male and female athletes with a history of two or more concussions, compared to athletes with no concussion history. This study was initially excluded because the focus of the review was moderate-severe TBI, but the task was similar to the morph task described in Rigon et al (26), so results might provide an informative comparison.…”
Section: Sex Differences In Social Cognition In Adults With Tbimentioning
confidence: 99%
“…These findings demonstrate striking sex differences in the persistent changes in basal gene expression after a subchronic immune challenge. (Importantly, this suggests that differential vulnerability to cognitive decline, memory impairments, and affective disorders (Himanen et al, 2006;Hogue et al, 2003;Lavoie et al, 2017;Léveillé et al, 2017;Liossi et al, 2009;Niemeier et al, 2007;Rainville and Hodes, 2018;Suarez et al, 2015) after illness or injury may be mediated by sex differences in the changes in gene expression and transcriptional regulation that persist long after immune challenge.…”
Section: Discussionmentioning
confidence: 99%